Mastering OpenCV 4 with Python : a practical guide covering topics from image processing, augmented reality to deep learning with OpenCV 4 and Python 3.7 /: a practical guide covering topics from image processing, augmented reality to deep learning with OpenCV 4 and Python 3.7. (2019) - Fernández Villán, Alberto
No abstract available